Answer:
Step-by-step explanation:
(5+x)+12
Step-by-step explanation:
<u>Given </u><u>:</u><u>-</u>
And we need to solve the equation using Substituting method . So on taking the first equation ,
<u>Put </u><u>this</u><u> </u><u>value</u><u> </u><u>in </u><u>(</u><u>ii)</u><u> </u><u>:</u><u>-</u><u> </u>
<u>Put </u><u>this</u><u> </u><u>Value</u><u> </u><u>in </u><u>(</u><u>I)</u><u> </u><u>:</u><u>-</u><u> </u>
<u>Hence</u><u> the</u><u> </u><u>Value</u><u> </u><u>of </u><u>x </u><u>is </u><u>2</u><u>1</u><u> </u><u>and </u><u>y </u><u>is </u><u>(</u><u>-</u><u>6</u><u>)</u><u> </u><u>.</u>
Answer:
thanks for any information you are very important the answers to your questions are answered me about human
Step-by-step explanation:
you can make the direction of economics class is study about the answers the question
Answer: n = -2
Step-by-step explanation:
3n +2(n + 2) = 9n + 12
(simplify 2(n + 2)) =
3n + 2n + 4 = 9n + 12
(subtract 9n from both sides)
3n + 2n - 9n + 4 = 12
-4n + 4 = 12
(subtract 4 from both sides)
-4n = 8
(divide -4 from both sides)
n = -2